2013
DOI: 10.1039/c3ob41244j
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, biophysical and primer extension studies of novel acyclic butyl nucleic acid (BuNA)

Abstract: A novel nucleic acid analogue called acyclic (S)-butyl nucleic acid (BuNA) composed of an acyclic backbone containing a phosphodiester linkage and bearing natural nucleobases was synthesized. Next, (S)-BuNA nucleotides were incorporated in DNA strands and their effect on duplex stability and changes in structural conformation were investigated. Circular dichroism (CD), UV-melting and non-denatured gel electrophoresis (native PAGE) studies revealed that (S)-BuNA is capable of making duplexes with its complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…Lately, there has been an explosion in the number of investigated candidates [47]. We have recently reported on the base-pairing properties of isoGNA, an isomer of glycerol derived nucleic acid (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, there has been an explosion in the number of investigated candidates [47]. We have recently reported on the base-pairing properties of isoGNA, an isomer of glycerol derived nucleic acid (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As some polymerases are known to display this activity in the presence of manganese at the expense of fidelity (Myers and Gelfand 1991;Grabko et al 1996), the Bst DNA polymerase does not require any special buffer conditions and is, therefore, useful in amplification reactions with RNA templates. In addition, it has been found that the Bst DNA polymerase can accept a very wide range of unusual nucleic acids as templates (Chaput et al 2003;Jackson et al 2019) and incorporates modified nucleotides (Kumar et al 2013;R€ othlisberger et al 2017). The great impact in isothermal amplification methods of the Bst DNA polymerase, and thus its commercial success, has led to the development of modified versions comprising useful features such as "warm start", improved thermal stability, and reverse transcriptase activity (Lee et al 2016).…”
Section: Dna Polymerasesmentioning
confidence: 99%
“…Kumar et al. designed butyl nucleic acid (BuNA), another isomer of GNA [38] . The C2 linker of the main chain in GNA is extended to a C3 linker in BuNA, corresponding to the number of atoms in the ribose scaffold in DNA and RNA (Figure 5).…”
Section: Negatively Charged Acyclic Xna Oligomersmentioning
confidence: 99%